The genus Creaserinus Hobbs, 1973 (Decapoda: Cambaridae) in Texas - Johnson, Daniel P.; Stern, David B.; Crandall, Keith A. (Zootaxa, 2021)
Presented is an account of the crayfish genus Creaserinus Hobbs, 1973 for Texas, based on materials gathered during a 13-year survey of the state. Home to Texas are six members of the genus, including C. hedgpethi (Hobbs, 1948) stat. rev., n. comb., which is resurrected from the synonymy of C. fodiens; and five species new to science described herein, including C. brevistylus n. sp., C. clausus n. sp., C. crenastylus n. sp., C. limulus n. sp., and C. trinensis n. sp. Collections of these species except for C. trinensis n. sp. were previously known and studied but ascribed to C. fodiens (Cottle, 1863), which is removed from the fauna of the state. Support for the taxonomic acts comes from genetics, morphology, distribution, life history, habitat, and syntopy. Accounts are provided for each species and include illustrations and information on distribution, color pattern, relationships, life history, ecology, size, variations, and crayfish associates. A key to the species in the state based on form I males is provided. Creaserinus limulus n. sp. is extraordinary in that a majority of its populations sampled have been composed mostly or entirely of females. Additions to the faunas of Texas’s neighboring states include C. clausus n. sp. (Louisiana), C. crenastylus n. sp. (Louisiana), and C. limulus n. sp. (Arkansas and Oklahoma).